2007
DOI: 10.1177/00084174070740s306
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Potential of the International Classification of Functioning, Disability and Health to Identify Barriers to and Facilitators of Consumer Participation

Abstract: The ICF can support the identification of a broad range of external barriers and facilitators relevant to participation and of interest to occupational therapy. However, therapists must use other strategies to gain a comprehensive understanding of the nature, extent and consequences of barriers and facilitators that may exist in a given

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…According to Nordenfelt (135) the component activity/participation could remain uniform and could be qualified and called action and thereby be relevant in the rehabilitation context. A potential use of ICF was found in articles focusing on assessments of participation barriers and facilitators (81). The value of ICF was described as a method of categorizing the activity and participation component in relation to assistive technology (42,43,47,84) and appropriate in rehabilitation, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Nordenfelt (135) the component activity/participation could remain uniform and could be qualified and called action and thereby be relevant in the rehabilitation context. A potential use of ICF was found in articles focusing on assessments of participation barriers and facilitators (81). The value of ICF was described as a method of categorizing the activity and participation component in relation to assistive technology (42,43,47,84) and appropriate in rehabilitation, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…How to deal with the two concepts will be explored through the continuing use of ICF. Further, it was found that ICF did not completely capture the complexity of participation (81). The level of detail and structure of environmental factors (67,78) need to be clarified, e.g.…”
Section: Described Limitations and Suggestions For Developmentmentioning
confidence: 99%
See 3 more Smart Citations